Process Optimization of Steam Explosion Parameters on Multiple Lignocellulosic Biomass Using Taguchi Method—A Critical Appraisal - Walker, David J.; Gallagher, Joe; Winters, Ana; Somani, Abhishek; Ravella, Sreenivas R.; Bryant, David N. (Frontiers in Energy Research, 2018)
Xylitol is a low calorie sweetener that can be produced through a bioconversion approach from lignocellulosic biomass that requires pretreatment prior to the bioconversion of xylose to xylitol. Steam explosion (SE) is an industrially scalable pretreatment (PT) process with the potential to liberate xylose monomers, however SE-PT has not been optimised for xylose release from multiple feedstock. The effect of pressure, substrate weight, phosphoric acid loading concentration and residence time on four feedstock (wheat straw (WS), corn stover (CS), Miscanthus (M), and willow (W)) for xylose release and minimal fermentation inhibitor productions (furfural and 5-hydroxymethylfurfural (HMF)) was investigated using the Taguchi methodology for design of experiment (DoE) with variation at four levels (44). An L16 orthogonal array design was utilised and all factors indicated influence on xylose release and inhibitor formation and the resulting xylose rich hydrolysate assessed for bioconversion to xylitol.. The L16 DoE gave hydrolysates containing 75-95% of xylose content in the original biomass, whilst retaining cellulose and lignin components in the fibre. The level of inhibitors were within boundary limits to enable microbial fermentation of the hydrolysates to xylitol. Fine tuning of the overall evaluation criteria (OEC) model imbibing 1.5 kg feedstock in 1.2% w/v orthophosphoric acid, 12 bar(g) and 6 minutes residence time resulted in 90% xylose recovery and production of >1000 L of wheat straw hydrolysate for bioconversion to xylitol. The advantages and limitations of the Taguchi OEC model and further improvements to this process are discussed in a biorefining context